Sosnovskio barščio (Heracleum sosnowskyi Manden.) paplitimas ir kontrolė Klaipėdos rajone - Markaitytė, Eglė (Jaunųjų mokslininkų darbai, 2023)
Every year, new sites of unwanted plants are recorded. The best known invasive plant in Lithuania – Sosnowsky’s hogweed (Heracleum sosnowskyi Manden.) – is widespread in Klaipėda district. Its abundant thickets change the species structure of communities, especially in grassland habitats. In addition, the plant is hazardous to skin and human health and damages farm animals. Mass eradication is being carried out in Lithuania, but if the right control method is chosen, it can ensure a lasting result that prevents the further spread of Sosnowsky’s hogweed. The aim of this study is to compare the results of 3 years of eradication with an area where no intensive eradication has been carried out. The results showed that mechanical and chemical eradication is more effective than mowing alone. Recommendations have also been made that will allow a more careful choice of control measures to reduce the risk of spreading invasive plants.
Keywords: Sosnovskio barštis; Heracleum sosnowskyi; Klaipėdos rajonas; invazinis augalas; naikinimas; šalinimas; bioįvairovė; kontrolė